Trunk Control in Children With Ataxic Cerebral Palsy. Issue 5 (October 2019) - Seyyar, Gulce Kallem; Aras, Bahar; Aras, Ozgen
This study aimed to investigate the clinical characteristics of trunk control in children with ataxic cerebral palsy (CP). We included 15 children with ataxic CP with a mean age of 9.46 years ( SD =  1.08 years, 5–17 years) and 15 healthy children with a mean age of 9.06 years ( SD  = 0.84 years, 5–13 years). While the small sample size and large age range used here were not ideal for generalizability, they were made necessary by the rarity of this clinical sample. We used the Gross Motor Function Classification System Expanded and Revised (GMFCS-E&R) to classify the children's functional levels, and we tested trunk control with the Trunk Control Measurement Scale (TCMS). We then used the Gross Motor Function Measurement-88 (GMFM-88) to assess their gross motor functions. We compared the total and subscale scores of the TCMS in healthy children and children with ataxic CP by using the Mann–Whitney U Test. We also analyzed differences between TCMS scores according to the children's GMFCS levels with the Mann–Whitney U Test and also compared TCMS scores with the GMFM-88 by means of Spearman correlation analysis. Spearman correlation analysis was used to compare the scores of the TCMS with the GMFM-88. Our results showed that healthy children showed significantly higher scores than children with ataxic CP in total and subscale scores of TCMS ( p  < .05).There was no significant difference between the TCMS scores in children of different GMFCS levels, but the GMFM-88B subscale was signiﬁcantly correlated with the static sitting balance ( rho  = .568, p  < .05) and dynamic sitting balance ( rho  = .547, p  < .05) TCMS subscales and with the TCMS total score ( rho  = .590, p  < .05). We concluded that trunk control, especially its dynamic aspects, was impaired in children with ataxic CP.